If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-4e-19=-3-6e
We move all terms to the left:
-4e-19-(-3-6e)=0
We add all the numbers together, and all the variables
-4e-(-6e-3)-19=0
We get rid of parentheses
-4e+6e+3-19=0
We add all the numbers together, and all the variables
2e-16=0
We move all terms containing e to the left, all other terms to the right
2e=16
e=16/2
e=8
| 23-2e=8e-37 | | 21+9e=-28-5e | | -11-2e=-27+6e | | 7b-85=180 | | 16+6e=3e-8 | | -7e+9=-17-5e | | -8x-10-x=-12x+20 | | 0.5y-1.25=3.5 | | 400=-10x | | -4x71=43 | | 70+x+32=90 | | 8+5v=38 | | 26=y+19 | | -4.2(x)=2.1 | | 1.4*12=y | | 2/4f+20=120 | | 5x-18=15x-12=180 | | 4x-1=3x+3=180 | | 2=3l/4 | | y=7.5+40 | | 25x10=300 | | 8=u/2-12 | | 3(6x+2)=2(9x-1) | | 6000+75*(x/90)=x | | x^2-2=83 | | 0.45x+3=0.3x+2 | | x^2/(2)=83 | | 3x=17/12 | | 20+2(3x+10)=2x | | x^2/2=83 | | 10r=1.000 | | 5.8/3x+6=3.8x+4.32 |